2008
DOI: 10.1080/07294360802406817
|View full text |Cite
|
Sign up to set email alerts
|

Raising the in‐class participation of Asian students through a writing tool

Abstract: This paper discusses the use of written communication as a tool to promote the participation of Asian students. It is suggested that teachers can unlock active participation through the use of written communication. To support this stance, the paper reviews existing work, and discusses empirical evidence collected from a large student survey carried out in Singapore and an example of the successful technique implemented by the author in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The previous studies found that Asian students tend to have low participation in class (Biggs 1999;Tani 2008). Although students study hard, they do not actively display their passion and enthusiasm in the class.…”
Section: Socio-cultural Context Of Engagementmentioning
confidence: 91%
See 1 more Smart Citation
“…The previous studies found that Asian students tend to have low participation in class (Biggs 1999;Tani 2008). Although students study hard, they do not actively display their passion and enthusiasm in the class.…”
Section: Socio-cultural Context Of Engagementmentioning
confidence: 91%
“…Although students study hard, they do not actively display their passion and enthusiasm in the class. Tani (2008) argued that this behavior might be influenced by Asian culture, which is mainly based on Confucian tradition emphasizing harmony over conflict and collective behavior rather than individual self-expression. Korean students, along with other Asian students-especially those from East Asia sharing Confucian values-tend to behave placidly in class, exhibit low participation in campus activities, and have limited interaction with faculty (Ko 2011).…”
Section: Socio-cultural Context Of Engagementmentioning
confidence: 99%
“…The questionnaire administered at YLLSoM was an adaptation of a survey carried out across most faculties at NUS and UNSW in 2004 and 2005, respectively, as part of an international project focusing on students' learning experiences and expectations in Singapore and Australia (Tani et al 2006a(Tani et al , 2006bTani 2008).…”
Section: Questionnairementioning
confidence: 99%
“…This includes critical and creative thinking, written communication, and flexibility to build up intercultural knowledge and capacity that can be applied and transferred across different languages, disciplines, cultures, professions and life circumstances (Stephens, 2009). Teaching and learning to support intercultural capability takes place in both domestic and international contexts and has gained importance in response to the challenge of globalization (Crabtree and Sapp, 2004;Tani, 2008;Lutz, 2010).…”
Section: Introductionmentioning
confidence: 99%